Mercury, Vaccines, and Autism: One Controversy, Three Histories - Baker, Jeffrey P. (American Public Health Association, 2008)
The controversy regarding the once widely used mercury-containing preservative thimerosal in childhood vaccines has raised many historical questions that have not been adequately explored. Why was this preservative incorporated in the first place? Was there any real evidence that it caused harm? And how did thimerosal become linked in the public mind to the “autism epidemic”? I examine the origins of the thimerosal controversy and their legacy for the debate that has followed. More specifically, I explore the parallel histories of three factors that converged to create the crisis: vaccine preservatives, mercury poisoning, and autism. An understanding of this history provides important lessons for physicians and policymakers seeking to preserve the public’s trust in the nation’s vaccine system.